An exploratory study on the sperm ratio in dogs: repeatability over time and some reproductive effects - Parma, Pietro; Groppetti, Debora; De Lorenzi, Lisa; Bronzo, Valerio; Vera d'Aragona, Isabella; Pecile, Alessandro (Archives of Veterinary Science, 2023)
Mechanisms that regulate sexual chromosome distribution in the canine ejaculate are not quite understood with no data about both its variation over time and the effect on reproductive parameters. With the aim to deepen these aspects, ten purebred male dogs, aged between 1.5 and 8.5 years, underwent digito-digital semen collection every three months throughout one year. A quantitative real-time PCR method was used to measure the sperm-sex ratio. The sperm-sex ratio was slightly female-biased without a significant difference throughout the year, albeit with some individual dynamic fluctuation over time. The total number of spermatozoa (P < 0.05) but not serum testosterone concentration nor the age of the dog was related to the sperm-sex ratio. In particular, dogs with a lower spermatozoa rate showed a greater number of spermatozoa in the ejaculate than dogs with a higher rate. A decreasing trend of X spermatozoa rate was also observed in dogs younger than 5 years of age. Quantitative real-time PCR proved to be an accurate, practical, and reliable method for determining the sperm-sex ratio in dogs. Further studies on a large scale could help to deepen the factors involved in the sperm-sex ratio and consequently in the offspring-sex ratio, opening new frontiers in canine andrology.